Corrosion Inhibition of Two New Sulfur - Containing Mannich Bases on N80 Steel in Hydrochloric Acid - HU Shan, WANG Ren-fang, YANG Ting, SHI Dong-po, LI Ke-hua, LI Yan-jun (Cailiao Baohu, 2021)
Oil well acidification is an important technology to increase the flow of oil, but acid liquid will cause serious corrosion of oil pipelines, resulting in the serious economic losses and safety hazards. In order to prevent the corrosion of metals in acidic media, two sulfur-containing Mannich bases corrosion inhibitors (HA, HB) were synthesized by using formaldehyde/benzaldehyde, acetophenone and thiosemicarbazide as basic materials. The weight loss method and electrochemical test method were used to study the corrosion inhibition performance of HA and HB on N80 steel in 10% hydrochloric acid, and the adsorption behavior of HA and HB corrosion inhibitor molecules on the Fe (001) crystal plane was theoretically discussed using molecular dynamics simulation. Results showed that the two inhibitor molecules had a good inhibitory effect on N80 steel, and the inhibitor effect of HB corrosion inhibitor was better than that of HA. In addition, the adsorption of two corrosion inhibitors on the surface of N80 steel conformed to the Langmuir adsorption isothermal model and the two kinds of corrosion inhibitors belonged to mixed inhibitors.